Operas that Contributed to the Emergence of Uzbek Opera - Husniddin Orifjonov (Research Parks Publishing LLC, 2022)
The works created by several composers who have contributed to the Uzbek opera art still form the basis of Uzbek opera. The analytical part of scientific works on the creation and development of Uzbek opera is considered here.